Anastrozole Loaded Nanostructured Lipid Carriers : Preparation and Evaluation - Alaa Abdul-Jabbar Hashim; Nawal A. Rajab (College of Pharmacy University of Baghdad, 2021)
Anastrozole (ANZ) is considered constitute of the fourth -generation of Non-steroidal aromatase blockage, ANZ has use for hormone receptor positive breast cancer in postmenopausal women. The serious side effects of ANZ including, vaginal dryness, hot flashes, irritability, breast tenderness and un-stability in circulation. Nanostructured lipid carriers (NLCs) have recently emerged as a multifunctional platform for drug delivery in cancer therapy. Five formula were composed of (200 mg of glyceryl monostearate, 40 mg of oleic acid , 1% (w/w) Tween 80, 1% (w/w) Poloxamer 407, 1% (w/w) soy lecithin and Vitamin E Polyethylene Glycol Succinate. The mean particle size, polydispersity index, zeta potential, entrapment efficiency, loading capacity range of optimum formula F05 (166±3.86 nm), (0.271±0.04), (-23.7±2.65 mV), (42.43±3.90%) and (1.23±0.35%) respectively that prepared by same above composition but higher amplitude value (70%). The in-vitro drug leakage study demonstrated intact formula through 5 hours, with an approximately 78.37% of the drug was encapsulated, that exhibit an anomalous release mechanism.